2021
DOI: 10.3390/su14010218
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Intention to Use Mobility as a Service: Case Study of Gyeonggi Province, Korea

Abstract: Mobility as a service (MaaS) integrates various transportation modalities and connects these modalities to enable users to travel from departure points to destination points. The objectives of this study were to analyze the factors influencing the intention to use MaaS and determine a direction for the implementation of this service. Hence, this study utilized an ordered probit model and marginal effect analysis. Specifically, a survey was conducted based on citizens living in Gyeonggi-do, South Korea, to prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The model analysis showed that people that spend 1 to 2 h per day on urban commuting have higher probability of selecting a MaaS system solution, while those that spend more than 2 h on their daily commute seemed less likely to choose a MaaS scheme. Such results correspond with the findings of Ko et al [51], and, as other studies suggest [52,53], car dependence seems to be a very important factor in individuals' choices. In addition, the inferential analysis showed that younger people have a higher probability of choosing a MaaS system.…”
Section: Discussionsupporting
confidence: 93%
“…The model analysis showed that people that spend 1 to 2 h per day on urban commuting have higher probability of selecting a MaaS system solution, while those that spend more than 2 h on their daily commute seemed less likely to choose a MaaS scheme. Such results correspond with the findings of Ko et al [51], and, as other studies suggest [52,53], car dependence seems to be a very important factor in individuals' choices. In addition, the inferential analysis showed that younger people have a higher probability of choosing a MaaS system.…”
Section: Discussionsupporting
confidence: 93%
“…Investigations on MaaS and en-vironment, e.g., [25,77,[80][81][82], evaluate the potential of MaaS to minimise car-dependency, encouraging a more sustainable mobility scheme and a more liveable metropolis. Papers on MaaS and people, e.g., [83][84][85][86][87], explore the user-centric nature of MaaS. They also assess the behavioural transition from an "ownership" to a "usership" regime proposed by the new model; MaaS expects end users to acquire mobility services, not the transport modes themselves.…”
Section: Maas and The Sc Dimensionsmentioning
confidence: 99%
“…A South Korean case study (a survey conducted in February 2020 with 781 participants) [10] identified factors influencing the MaaS use and included constructs for measuring intention to use MaaS and variables related to influential factors with a ordered probit model and estimating marginal effects. The study identified seven key variables from 11 tested, with user characteristics such as being male, from a lower income household, and existing public transit use showing greater intent to use MaaS.…”
Section: On Sensitive Transport Parameters Of Maas Usersmentioning
confidence: 99%